2012
DOI: 10.1177/193229681200600403
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Postprandial Glycemic Excursions following Insulin Lispro Delivered by Intradermal Microneedle or Subcutaneous Infusion

Abstract: This study indicates that ID insulin delivery is superior to SC delivery in speed of systemic availability and PK consistency and may improve postprandial glucose control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 46 publications
1
37
1
Order By: Relevance
“…Without comparable (i.e., identical) glucose/insulin levels in the last hour(s) prior to the intervention (i.e., ingestion of the meal/insulin application), the validity of comparing the results obtained on different study days is compromised. With the UFIs presented here, some meal-related studies fulfilling these requirements have been performed demonstrating their benefits also in comparison with RAIAs (see the other related manuscripts 18,25,30,48,49,54 ). One can envisage head-to-head comparisons involving two or more of the approaches presented in a given study under identical UFI conditions that would allow one to make clear statements about the pros and cons of the studied developments.…”
Section: Discussion and Outlookmentioning
confidence: 99%
See 1 more Smart Citation
“…Without comparable (i.e., identical) glucose/insulin levels in the last hour(s) prior to the intervention (i.e., ingestion of the meal/insulin application), the validity of comparing the results obtained on different study days is compromised. With the UFIs presented here, some meal-related studies fulfilling these requirements have been performed demonstrating their benefits also in comparison with RAIAs (see the other related manuscripts 18,25,30,48,49,54 ). One can envisage head-to-head comparisons involving two or more of the approaches presented in a given study under identical UFI conditions that would allow one to make clear statements about the pros and cons of the studied developments.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…The U.S.-based company Becton Dickinson (see the article by McVey and coworkers 25 in this special theme issue) is developing an insulin infusing product that applies the insulin by means of short insulin needles ("microneedles") into the dermis instead of the SC tissue.…”
Section: Intradermal Application Of the Insulinmentioning
confidence: 99%
“…[20][21][22][23] Alternative insulin delivery methods such as inhaled insulin and intradermal delivery with microneedles have been shown to confer ultra-fast-acting profiles during meal and insulin clamp studies. [24][25][26] Further studies are needed to determine whether the time-action profiles of rapid-acting insulin analogs can be accelerated even more by combining site warming with one or another of these alternative approaches.…”
Section: Discussionmentioning
confidence: 99%
“…These include micro-needle, intradermal infusion sets for pump therapy, [12][13][14][15] changes in excipients in RAIA formulations to accelerate insulin molecule monomerization 16 and treating the insulin infusion site with hyaluronidase to breakdown interstitial barriers to dispersion of injected liquids. 17 In comparison to these approaches, local warming relies on a relatively simple physiological approach which, in this study, we have demonstrated is suited for injection as well as pump therapy.…”
Section: Discussionmentioning
confidence: 99%